Этический аспект научных публикаций в условиях информационного взрыва (опыт химика) - Мчедлов-Петросян, Н.О. (Вісник НАН України, 2014)
В статье перечислены и кратко рассмотрены этические проблемы, последовательно возникающие в ходе публикации научных результатов, — начиная от проблем авторства, соавторства и взаимодействия с редакциями журналов и заканчивая проблемами оценивания результативности
научных работников на основе их публикаций. Обсуждение проведено на
примере научных работ в области химии. Автор стремился особо выделить
специфику новых проблем, возникающих в условиях нынешнего информационного взрыва. У статті перелічено та стисло розглянуто етичні проблеми, які послідовно виникають у процесі публікації наукових результатів, — починаючи від проблем авторства, співавторства та взаємодії з редакціями журналів і завершуючи проблемами оцінювання результативності науковців на основі їх публікацій. Обговорення проведено на прикладі наукових робіт у галузі хімії. Автор намагався особливо виділити специфіку нових проблем, які постають в
умовах сучасного інформаційного вибуху. The ethical problems arising during the publication of scientific articles are listed and briefly considered. The author
tried to stress on the new peculiarities resulting from the today’s information burst. The ethics of the authorship and coauthorship,
of the reviewing process and the cooperation with the editorial boards is successively discussed. Special attention
is paid to such issues as citation and citation indexes, in particular the h-index, and the impact factors, IF, of scientific
journals. Finally, the ethical aspects of the evaluation of the scientists basing on the numerical characteristics of
their publication activity are discussed. To the author’s viewpoint, the main problem consists in the failing ability of the
scientific community and even more so officials/bureaucrats to estimate the actual scientific value of the publications.
The statistical data reflecting the total number of published works, citations, IF of the journals, etc., are interesting and
useful, but none of them should be used as a sole criterion of the productivity of a scientist.